Reusability of dictionaries in the compilation of NLP lexicons - Dias-da-Silva, B. C.; de Oliveira, M. F.; de Moraes, H. R. (Springer, 2003)
This paper discusses particular linguistic challenges in the task of reusing published dictionaries, conceived as structured sources of lexical information, in the compilation process of a machine-tractable thesaurus-like lexical database for Brazilian Portuguese. After delimiting the scope of the polysemous term thesaurus, the paper focuses on the improvement of the resulting object by a small team, in a form compatible with and inspired by WordNet guidelines, comments on the dictionary entries, addresses selected problems found in the process of extracting the relevant lexical information form the selected dictionaries, and provides some strategies to overcome them.